Research on incentive mechanisms for veterans’ participation in grassroots governance: An analysis based on behavioral expectations - Shuqiong Wang; Zhao Zhang (PLoS ONE, 2026)
Under the modernization of grassroots governance, veterans constitute a high-quality human resource for enhancing grassroots social governance capacity. Drawing on questionnaire survey data from 525 veterans in Guizhou Province, China, this study identifies three distinct veteran groups using latent class analysis (LCA): Utilitarian (51.3%), Mission-Oriented (23.8%), and Development-Focused (24.9%). Empirical results reveal clear heterogeneity in policy responsiveness and behavioral mechanisms across groups. First, the Utilitarian group responds most strongly to Subsidies, with participation behavior predominantly driven by economic rationality. Second, the Mission-Oriented group demonstrates honor-driven motivations, with symbolic recognition playing a central role in stimulating governance engagement. Third, the Development-Focused group prioritizes career advancement and exhibits significant responsiveness to promotion-related incentives. Based on these findings, this study constructs a mediation model of “Policy Instruments (PI)—Behavioral Expectations (BE)—Participation Behavior (PB)” and proposes an intervention pathway centered on “expectation diagnosis” and “instrument matching.” By revealing the internal mechanism through which policy instruments (PI) influence participation behavior (PB) via Behavioral expectations (BE), this research provides empirical evidence and theoretical insights for shifting incentive strategies from “uniform provision” to “precision adaptation.”.